Soft Tissue Edema Around Musculoskeletal Sarcomas at Magnetic Resonance Imaging. (1997) - Panicek, David M.; Schwartz, Lawrence H.
Abstract : The presence of soft tissue edema around a malignant musculoskeletal neoplasm can interfere with accurate local tumor staging at magnetic resonance imaging. This article discusses and illustrates such edema, emphasizing means for avoiding misinterpretation of edema and subsequent overstaging.